Alpelisib plus fulvestrant in PIK3CA-mutated, hormone receptor-positive advanced breast cancer after a CDK4/6 inhibitor (BYLieve): one cohort of a phase 2, multicentre, open-label, non-comparative study. Issue 4 (April 2021) - Rugo, Hope S; Lerebours, Florence; Ciruelos, Eva; Drullinsky, Pamela; Ruiz-Borrego, Manuel; Neven, Patrick; Park, Yeon Hee; Prat, Aleix; Bachelot, Thomas; Juric, Dejan; Turner, Nicholas; Sophos, Nickolas; et al.
Summary: Background: Alpelisib, a PI3Kα-selective inhibitor and degrader, plus fulvestrant showed efficacy in hormone receptor-positive, HER2-negative, PIK3CA -mutated advanced breast cancer in SOLAR-1; limited data are available in the post-cyclin-dependent kinase 4/6 inhibitor setting. BYLieve aimed to assess alpelisib plus endocrine therapy in this setting in three cohorts defined by immediate previous treatment; here, we report results from cohort A. Methods: This ongoing, phase 2, multicentre, open-label, non-comparative study enrolled patients with hormone receptor-positive, HER2-negative, advanced breast cancer with tumour PIK3CA mutation, following progression on or after previous therapy, including CDK4/6 inhibitors, from 114 study locations (cancer centres, medical centres, university hospitals, and hospitals) in 18 countries worldwide. Participants aged 18 years or older with an Eastern Cooperative Oncology Group performance status of 2 or less, with no more than two previous anticancer treatments and no more than one previous chemotherapy regimen, were enrolled in three cohorts. In cohort A, patients must have had progression on or after a CDK4/6 inhibitor plus an aromatase inhibitor as the immediate previous treatment. Patients received oral alpelisib 300 mg/day (continuously) plus fulvestrant 500 mg intramuscularly on day 1 of each 28-day cycle and on day 15 of cycle 1. The primary endpoint was the proportion of patients alive without disease progression at 6 months per local assessment using Response Evaluation Criteria in Solid Tumors, version 1.1, in patients with a centrally confirmed PIK3CA mutation. This trial is registered with ClinicalTrials.gov, NCT03056755 . Findings: Between Aug 14, 2017, and Dec 17, 2019 (data cutoff), 127 patients with at least 6 months' follow-up were enrolled into cohort A. 121 patients had a centrally confirmed PIK3CA mutation. At data cutoff, median follow-up was 11·7 months (IQR 8·5–15·9). 61 (50·4%; 95% CI 41·2–59·6) of 121 patients were alive without disease progression at 6 months. The most frequent grade 3 or worse adverse events were hyperglycaemia (36 [28%] of 127 patients), rash (12 [9%]), and rash maculopapular (12 [9%]). Serious adverse events occurred in 33 (26%) of 127 patients. No treatment-related deaths were reported. Interpretation: BYLieve showed activity of alpelisib plus fulvestrant with manageable toxicity in patients with PIK3CA -mutated, hormone receptor-positive, HER2-negative advanced breast cancer, after progression on a CDK4/6 inhibitor plus an aromatase inhibitor. Funding: Novartis Pharmaceuticals.